A 3D multi-segment thermoregulation model of the hand with realistic anatomy: Development, validation, and parametric analysis. (15th August 2021) - Zhang, Mengying; Li, Rui; Li, Jun; Wang, Faming; Subramaniam, Shankar; Lang, James; Passalacqua, Alberto; Song, Guowen
Abstract: A three-dimensional (3D) multi-segment hand-specific thermoregulation model was developed as a fundamental tool for spatial and temporal skin temperature prediction. Cold-induced vasodilation in fingers was simulated by superimposing symmetrical triangular waveforms onto the basal blood flow. The model used realistic anatomical, physiological, and thermo-physical information of a standard human hand and forearm. The inhomogeneity of hand thermal and physiological properties was considered by dividing it into 17 segments: palm, dorsal, forearm, and five fingers, with each finger subdivided into fingertip, middle segment, and finger root except for the thumb, which has no middle segment. Each segment contained a bone core and an outer soft tissue layer. 3D scanning technology was employed to develop the geometrically realistic model of the hand and the bone. The thermo-physical and physiological properties of each segment and layer were obtained from a photogrammetric analysis of anatomic atlases and from literature. Heat transfer throughout the hand by metabolism, blood perfusion, and conduction between the tissue was considered. Heat loss by convection and radiation from the skin and the protective effects of gloves were also included in the model. The model showed good agreement with experimental data from the literature. The developed 3D hand model fills the knowledge gap and builds a bridge between existing knowledge of the hand's physiology and its application, providing a science-based tool for decision making. The understanding from model studies may also help enhance the wearer's working efficiency, safety, health, and wellbeing while working in indoor and outdoor cold environments. Highlights: A 3D multi-segment hand-specific thermoregulation model is developed. The model is a more realistic representation of the hand's anatomy and physiology. The model accounts for the hand's inhomogeneity by dividing it into 17 segments. Cold-induced vasodilation (CIVD) in fingers was simulated. The model predicts the spatial and temporal skin temperature accurately.